Revolutionizing prostate cancer care: Unravelling the effects of varied surveillance intensities on treatment quality and patient well-being. - Anika Rastogi (The Young Researcher)
To validate three different Active Surveillance Care Pathways for men with prostate cancer, Low-Intensity, Intermediate-Intensity, and High-Intensity schedules were evaluated. Three factors related to the appropriateness and quality of care were considered: patient adherence to the schedule, negative biopsy incidence, and time to detection of significant cancer. The intermediate- intensity schedule had the best adherence as 40.9% adhered to their schedule at the confirma- tory biopsy and 15.9% adhered to the 36-month surveillance biopsy, showing that it was the least burdensome. In terms of negative biopsy rate, the Low-Frequency and High-Frequency Schedules were shown to be most effective in their patient populations. Finally, the High-Frequency Schedule had the earliest time to detection of significant cancer (n= 691 days) showing the best clinical outcomes. Ultimately, further investigation is needed to determine how to increase adherence to the biopsy schedules that lead to the best clinical outcomes.